The influence of strontium release rate from bioactive phosphate glasses on osteogenic differentiation of human mesenchymal stem cells. Issue 3 (March 2018) - Stefanic, M.; Peroglio, M.; Stanciuc, A.-M.; Machado, G.C.; Campbell, I.; Kržmanc, M. Maček; Alini, M.; Zhang, X.
Graphical abstract: Abstract: Strontium-doped bioactive phosphate glasses (P-glasses) of general composition 40(P2 O5 )–25(CaO)–5(Na2 O)–(30-x)MgO–x(SrO) (x = 0, 1, 5, 10) were fabricated via melt-quenching technique and effects of strontium (Sr) content on P-glass properties were systematically studied, including glass structure and density, thermal properties, solubility and cytocompatibility with human mesenchymal stem cells (hMSCs). Sr-doping resulted in the weakening of glass network and a decrease in glass transition and melting temperatures. P-glasses maintained physiological pH on immersion in simulated body fluid and exhibited sustained ion release for up to ten weeks. All P-glasses tested were cytocompatible with hMSCs. Sr 2+ release upregulated the genes associated with hMSC osteogenic differentiation; expression levels of early markers (RUNX2, COL 1) were proportional to the amount of Sr 2+ in the P-glasses, while expression of late markers (AlP, OC) was the highest for the P-glass containing 5 mol% Sr. It was concluded that Sr-doped P-glasses promoted osteogenic differentiation of hMSCs and have considerable potential for bone tissue regeneration.